LiNb03 polymer composite thin film: towards it's preparation - Ahmad Mukifza Harun; Vaughn, Gareth M.; Brown, Andrew P.; Comyn, Tim P.; Bell, Andrew J. (2010)
Lithium Niobate (LiNbO3) is a well-known ferroelectric material with excellent nonlinear piezoelectric, pyroelectric and electro-optic properties. However, there is little research conducted exploring its application in thin film composites. Here we describe the preparation and characterization of LiNbO3 , as a precursor to its use in polymer composites. LiNbO3 has been prepared via a molten salt route, which has been previously shown to be one of the simplest means to prepare pure and stoichiometric LiNbO3 nanocrystals.